Bundling method to treat extensive thumb fingertip pulp incisions – a case report - Li, Shao-Guang; Wang, Xiao-Jian; Huang, Jie-Feng (Vojnosanitetski pregled, 2022)
Introduction. Thumb fingertip injuries, often combined with phalanx fracture or torn ligament, are very common. The focus of treatment is on how to rebuild the function and shape of the thumb. Single thumb fingertip pulp injury is more common. However, due to the diverse type of injury, no uniform treatment guideline is described in the literature. Case report. A patient with extensive thumb fingertip pulp incisions, which looked like multiple parallel wounds, was admitted to our Emergency Department. We used the method of bundling to maintain the shape of the fingertip. A single suture to pass through all the incisions was performed and then the suture was tied outside the skin. After that, we bandaged them with sterile bandages. Finally, good contour and fingertip function were restored. Conclusion. We successfully used the bundling method to treat patient with extensive thumb fingertip pulp incisions.